2003
DOI: 10.1093/pcp/pcg128
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Isoforms of NADPH:Protochlorophyllide Oxidoreductase (POR), PORB and PORC, in Arabidopsis thaliana

Abstract: ; NADPH:protochlorophyllide oxidoreductase (POR) catalyzes the light-dependent reduction of protochlorophyllide. To elucidate the physiological function of three differentially regulated POR isoforms (PORA, PORB and PORC) in Arabidopsis thaliana, we isolated T-DNA tagged null mutants of porB and porC. The mature seedlings of the mutants had normal photosynthetic competencies, showing that PORB and PORC are interchangeable and functionally redundant in developed plants. In etiolated seedlings, only porB showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 41 publications
5
109
0
1
Order By: Relevance
“…We selected the porB mutants because they represent the isoform that is constantly expressed in darkness and light, while PORC is light-dependently expressed and PORA is expressed only in etiolated tissue (Masuda et al, 2003). Interestingly, porB mutants actually express higher levels of LIL3 than the wild type.…”
Section: Altered Levels Of Chl Synthesis Proteins In Porbdeficient Mumentioning
confidence: 99%
“…We selected the porB mutants because they represent the isoform that is constantly expressed in darkness and light, while PORC is light-dependently expressed and PORA is expressed only in etiolated tissue (Masuda et al, 2003). Interestingly, porB mutants actually express higher levels of LIL3 than the wild type.…”
Section: Altered Levels Of Chl Synthesis Proteins In Porbdeficient Mumentioning
confidence: 99%
“…These include phosphoglycerate kinase (AT1G56190), Fru-bisP aldolase (AT2G21330) Fru-1,6-bisphosphatase (AT3G54050), sedoheptulose-1,7-bisphosphatase (AT3G55800), phosphoribulokinase (AT1G32060), phosphoglycolate phosphatase (AT5G36700), Gly cleavage system H protein (AT1G32470), Gly cleavage system H protein 1 (AT2G35370), and carbonic anhydrases (AT3G52720, AT4G33580, and CA1). Furthermore, there is a repression of genes for enzymes that mediate key steps in the biosynthesis of photosynthetic pigments, such as chlorophyll (PORB and PORC; 5-to 10-fold) and carotenoids (PSY and GGPS; 3-and 2-fold, respectively); PORB and PORC are crucial for the photoconversion of protochlorophyllide to chlorophyllide, which is then converted to chlorophyll (Masuda et al, 2003). Likewise, PSY is the key regulatory step of carotenogenesis in plastids (Hirschberg, 2001).…”
Section: Photosynthesismentioning
confidence: 99%
“…The proteins encoded by these two genes are known to be the major components of prolamellar bodies in etioplasts of dark-grown seedlings (Masuda et al, 2003). It has been reported that both mRNAs are accumulated in etiolated seedlings but only PORB mRNA continues to accumulate in light-grown plants, while PORA mRNA rapidly disappeared after illumination.…”
Section: Characteristics Of the C2 And C3 Clustersmentioning
confidence: 99%